Determinants of exercise-induced oxygen desaturation including pulmonary emphysema in COPD: Results from the ECLIPSE study. (October 2016) - Andrianopoulos, Vasileios; Celli, Bartolome R.; Franssen, Frits M.E.; Pinto-Plata, Victor M.; Calverley, Peter M.A.; Vanfleteren, Lowie E.G.W.; Vogiatzis, Ioannis; Vestbo, Jørgen; Agusti, Alvar; Bakke, Per S.; Rennard, Stephen I.; MacNee, William; et al.
Abstract: Exercise-induced oxygen desaturation (EID) is related to mortality in patients with chronic obstructive pulmonary disease (COPD). We investigated: (1) the prevalence of EID; (2) the relative-weight of several physiological determinants of EID including pulmonary emphysema, and (3) the relationship of EID with certain patients' clinical characteristics. Data from 2050 COPD patients (age: 63.3 ± 7.1years; FEV1 : 48.7 ± 15.7%pred.) were analyzed. The occurrence of EID (SpO2 post ≤88%) at the six-minute walking test (6MWT) was investigated in association with emphysema quantified by computed-tomography (QCT), and several clinical characteristics. 435 patients (21%) exhibited EID. Subjects with EID had more QCT-emphysema, lower exercise capacity and worse health-status (BODE, ADO indexes) compared to non-EID. Determinant of EID were obesity (BMI≥30 kg/m 2 ), impaired FEV1 (≤44%pred.), moderate or worse emphysema, and low SpO2 at rest (≤93%). Linear regression indicated that each 1-point increase on the ADO-score independently elevates odds ratio (≤1.5fold) for EID. About one in five COPD patients in the ECLIPSE cohort present EID. Advanced emphysema is associated with EID. In addition, obesity, severe airflow limitation, and low resting oxygen saturation increase the risk for EID. Patients with EID in GOLD stage II have higher odds to have moderate or worse emphysema compared those with EID in GOLD stage III-IV. Emphysematous patients with high ADO-score should be monitored for EID. Highlights: About one in five COPD patients (21%) in the ECLIPSE cohort exhibited EID. Severe to very severe pulmonary emphysema is associated with EID. Advanced emphysema, obese BMI, severe airflow limitation, and low oxygen saturation at rest increase the risk for EID. Patients with EID in GOLD II have higher odds to have moderate or worse emphysema compared those with EID in GOLD III-IV. Emphysematous patients with high ADO-score should be monitored for EID.